(untitled) (International journal of medical sciences, 2026)
The adrenal glands play a crucial role in the regulation of stress responses and maintenance of homeostasis. In forensic medical practice, the evaluation of adrenal morphology is of particular importance in cases of nonviolent death, especially when external signs of injury are absent. The present study aims to assess morphological changes in the cells of the adrenal cortex and medulla in cases of nonviolent death and to determine their forensic significance. The material of the study included adrenal gland tissue samples obtained during medico-legal autopsies of individuals who died from nonviolent causes. Standard histological staining techniques and light microscopic examination were applied. The results revealed characteristic morphological changes, including dystrophic alterations, redistribution of lipid inclusions, vascular disturbances, and signs of functional exhaustion of the adrenal cortex, as well as stress-related changes in medullary cells during the terminal period. These findings indicate that morphological assessment of the adrenal glands may serve as an additional objective criterion in the forensic evaluation of nonviolent death when interpreted in conjunction with clinical and pathological data.